2011
DOI: 10.1071/he11153
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report – A qualitative study about smoking cessation with clients of community service organisations that work with disadvantaged families

Abstract: There is a need for smoking cessation support to be integrated into CSOs for disadvantaged families as clients are unlikely to seek support elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Other service providers include management and staff in prisons, homeless shelters and organisations, and members of the community. Thirteen qualitative studies 52 55 56 58 74 77 83 86 91 92 95 108 112 and one quantitative study 109 reported a perceived lack of support from health professionals regarding smoking cessation. Cases of family members and health professionals actively discouraging quit attempts and encouraging maintenance of smoking due to concerns about the individual's mental health 92 93 95 96 112 or because smoking was perceived to be the individual's only source of enjoyment 54 77 79 83 were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Other service providers include management and staff in prisons, homeless shelters and organisations, and members of the community. Thirteen qualitative studies 52 55 56 58 74 77 83 86 91 92 95 108 112 and one quantitative study 109 reported a perceived lack of support from health professionals regarding smoking cessation. Cases of family members and health professionals actively discouraging quit attempts and encouraging maintenance of smoking due to concerns about the individual's mental health 92 93 95 96 112 or because smoking was perceived to be the individual's only source of enjoyment 54 77 79 83 were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies examined factors influencing smokers’ quit intentions (Fagan & Augustson, 2007; Feng et al, 2010; Franco, Welsby, Eccleston, & Furber, 2011; Mathur & Singh, 2015; Sorensen et al, 2002). For example, for all or almost all examined racial/ethnic groups, longer quit attempts, daily smoking, and receiving advice to quit from a doctor were associated with higher odds of intending to quit (Soulakova, Li, & Crockett, 2017).…”
Section: Factors Associated With Intentions To Quitmentioning
confidence: 99%
“…Previous research has described the barriers to smoking cessation experienced by individuals living in disadvantaged areas [8,11,[15][16][17] and clients of community service organizations [18][19][20]. Among the broader sphere of groups at risk of social and economic disadvantage, specific subpopulations report unique barriers to quitting [4].…”
Section: Introductionmentioning
confidence: 99%